ANALYSIS OF PATIENT SATISFACTION LEVEL TOWARDS THE QUALITY OF REGISTRATION SERVICES AT THE OUTPATIENT COUNTER OF PROF. DR. H. ALOEI SABOE HOSPITAL, GORONTALO CITY - lestari, adinda; Ngabito, Yolanda; Moha , Lidya Paramitha (LP2M Universitas Bina Mandiri Gorontalo, 2024)
Study This aiming For know level satisfaction patient to quality service reviewed from dimensions quality services available at Prof. Dr. H. Aloei Saboe Regional Hospital , Gorontalo City. The method in study This use descriptive quantitative with technique data retrieval through distribution Questionnaire to patient take care road in Prof. Dr. H. Aloei Saboe Regional Hospital, Gorontalo City. Research Results show that that level satisfaction patient to quality services available at the counter take care road based on five dimensions quality very average service good . Level of suitability between hope and reality to the highest service accepted in the tangible dimension by (97%). And the level of conformity between hope and reality to lowest service received​​ is dimensions reabillity by (76%).